THE POTENTIAL OF AMELASIR TO RESTORING SANDY LAND INTO PRODUCTIVE PADDY FIELDS AT PT PIM FOSTERED VILLAGE - Yusra; Emmia Tambarta Kembaren; Usnawiyah; Suci Mahdianti; Nurul Ismi; Sri Wahyuni (CV. Radja Publika, 2023)
North Aceh district has 12,750 ha of idle land that has the potential to be planted with rice. This unused land becomes rice paddies because it has a large enough area and contains elements needed by rice plants. PT Pupuk Iskandar Muda implemented a program to turn sandy land into fertile rice fields called AMELASIR (Amelioration of Sandy Land) with an area of 278 m2. This program is carried out by offering intensive tillage and using ameliorants. The materials added were PIM organic fertilizer, clay, manure, rice straw compost, PIM Polivit and PIM Urea. The results of this program show an increase in rice yield from year to year. In the first growing season the harvest reached 3 tons/ha, in the second growing season it reached 3.45 tons/ha, and in the third growing season the harvest reached 4.5 tons/ha. This area has a faunal biodiversity index H' 3.22 and floral biodiversity H' 2.28. The conversion of idle land into paddy fields also increased the biodiversity of several interesting fauna species, namely 12 bird species, one reptile species, two mammal species, and 20 insect species. The AMELASIR program also made the soil more fertile for some trees so that four tree species, two pole species, eight sapling species and 16 seedling species grew in the area.